2018
DOI: 10.1073/pnas.1802501115
|View full text |Cite
|
Sign up to set email alerts
|

VirB8 homolog TraE from plasmid pKM101 forms a hexameric ring structure and interacts with the VirB6 homolog TraD

Abstract: SignificanceThe overproduction and purification of membrane proteins are intrinsically difficult, making their analysis challenging. We purified the TraE membrane protein from a bacterial conjugation system that is involved in plasmid transfer. Our results suggest that this protein forms hexamers with a central pore, and we also show that it binds to the TraD protein. The structure of TraE is completely different from that of the previously characterized periplasmic domain. This has intriguing implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…The structures are reminiscent of the mammalian nuclear transfer factor NTF2, a protein that also presents as a dimer and undergoes multiple protein–protein interactions . Exceptionally, TraE, a homologue of VirB8 from the conjugation plasmid pKM101, shows a similar structure but with an altered dimerization interface of its periplasmic domain , and the full‐length form of TraE forms a hexamer with a central pore . Likewise, DotI, an inner membrane protein from the Dot/Icm type IV secretion system that is known as a counterpart of VirB8, forms octameric rings in a periplasmic domain crystal, which has been proven to be an intrinsic property rather than a crystal packing artefact .…”
Section: Introductionmentioning
confidence: 99%
“…The structures are reminiscent of the mammalian nuclear transfer factor NTF2, a protein that also presents as a dimer and undergoes multiple protein–protein interactions . Exceptionally, TraE, a homologue of VirB8 from the conjugation plasmid pKM101, shows a similar structure but with an altered dimerization interface of its periplasmic domain , and the full‐length form of TraE forms a hexamer with a central pore . Likewise, DotI, an inner membrane protein from the Dot/Icm type IV secretion system that is known as a counterpart of VirB8, forms octameric rings in a periplasmic domain crystal, which has been proven to be an intrinsic property rather than a crystal packing artefact .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the stoichiometry of VirB8 was estimated to 12 in Conj-T4SS from E. coli R388 [40]. In line with, the purification of full-length TraE and TraM, a VirB8 homolog from pKM101 and R64, respectively, revealed that TraE and TraM forms hexamers in solution [39, 41]. Dissimilar to what was described in Gram-negative bacteria, VirB8-like proteins in Gram-positive bacteria are proposed to function as trimers.…”
Section: Discussionmentioning
confidence: 92%
“…We have previously used this approach to identify inhibitors of the VirB8 homolog TraE from the plasmid pKM101 conjugation system. We identified molecules that target a known inhibitor binding site on VirB8-like proteins, and we also identified a new binding site showing the potential for the discovery of bioactive molecules and of novel inhibitor target sites 23,24,33 .…”
Section: Resultsmentioning
confidence: 99%